Pediatrics adverse childhood experiences and related life events screener (PEARLS) and health in a safety-net practice. (October 2020) - Thakur, Neeta; Hessler, Danielle; Koita, Kadiatou; Ye, Morgan; Benson, Mindy; Gilgoff, Rachel; Bucci, Monica; Long, Dayna; Burke Harris, Nadine
Abstract: Background: Adverse Childhood Experiences (ACEs) are associated with behavioral, mental, and clinical outcomes in children. Tools that are easy to incorporate into pediatric practice, effectively screen for adversities, and identify children at high risk for poor outcomes are lacking. Objective: To examine the relationship between caregiver-reported child ACEs and related life events with health outcomes. Participants and setting: Participants (0–11 years) were recruited from the University of California San Francisco Benioff's Children Hospital Oakland Primary Care Clinic. There were 367 participants randomized. Methods: Participants were randomized 1:1:1 to item-level (item response), aggregate-level (total number of exposures), or no screening for ACEs (control arm) with the PEdiatric ACEs and Related Life Event Screener (PEARLS). We assessed 10 ACE categories capturing abuse, neglect, and household challenges, as well as 7 additional categories. Multivariable regression models were conducted. Results: Participants reported a median of 2 (IQR 1–5) adversities with 76 % (n = 279) reporting at least one adversity; participants in the aggregate-level screening arm, on average, disclosed 1 additional adversity compared to item-level screening (p = 0.01). Higher PEARLS scores were associated with poorer perceived child general health (adjusted B = −0.94, 95 %CI: −1.26, −0.62) and Global Executive Functioning (adjusted B = 1.99, 95 %CI: 1.51, 2.46), and greater odds of stomachaches (aOR 1.14; 95 %CI: 1.04–1.25) and asthma (aOR 1.08; 95 %CI 1.00, 1.17). Associations did not differ by screening arm. Conclusion: In a high-risk pediatric population, ACEs and other childhood adversities remain an independent predictor of poor health. Increased efforts to screen and address early-life adversity are necessary.